Iterative Project Processes Within Temporary Multi‐Organizations in Construction: The Self‐, Eco‐, Re‐Organizing Projects. Issue 1 (February 2016) - de Blois, Michel; Lizarralde, Gonzalo; De Coninck, Pierre
ABSTRACT: Theory‐based studies claim that informal processes interfere with the formal mechanisms and structures of projects in the construction sector. These processes structure and transform multi‐organizations. This four‐year case study reveals empirical evidence about how processes effectively evolve over time and affect formal mechanisms and structures. The results show: (1) the significant differences between what is planned and what actually unfolds in project processes; (2) how iterative processes overshadow linear ones; (3) how informality and "iterativity" eventually end up as self‐, eco‐, and re‐organizing projects and organizations, confirming that projects (re)create the very processes and structures that initiate them.